Correlation between sintering temperature and dwell time on structural and ferroelectric properties of NiTiO\(_3\)-CoFe\(_2\)O\(_4\) ceramics - Bac, Luong Huu; Dung, Dang Duc; Tuan, Nguyen Hoang; Thoan, Nguyen Hoang; Thang, Pham Van (Communications in Physics, 2024)
The 0.9NiTiO3-0.1CoFe2O4 ceramic was prepared by sol-gel method. The structural and ferroelectric properties of the ceramic were investigated. Structure of the materials was analyzed by X-ray diffraction and scanning electron microscopy. Fabricated materials consists of NiTiO3 with rhombohedral phase structure and CoFe2O4 with cubic structure. The effect of sintering temperature and dwell time on the phase, microsctructure and ferroelectric properties of the ceramics was investigated. As the sintering temperature and dwell time increased, the density of the bulk sample was improved. The material sample was sintered at 1200oC for 10 h with large particle size ( 6 µm), few pores and high density 97.5%. The composite material displayed ferroelectric properties, as evidence from the characteristic hysteresis loop observed in ferroelectric materials. At sintering temperatures of 1000°C and 1100°C for 2 and 5 h, the sample exhibited poor ferroelectric characteristics. However, when the sample was sintered at 1200°C for 10 h, a notable enhancement in ferroelectric properties was observed.